Clinical and economic outcomes of infective endocarditis. Issue 2 (February 2015) - Sunder, Simon; Grammatico-Guillon, Leslie; Baron, Sabine; Gaborit, Christophe; Bernard-Brunet, Anne; Garot, Denis; Legras, Annick; Prazuck, Thierry; Dibon, Olivier; Boulain, Thierry; Tabone, Xavier; Guimard, Yves; et al.
Abstract: Background: In France, the estimated annual incidence of infective endocarditis (IE) is 33.8 cases per million residents. Valvular surgery is frequently undergone. We report an epidemiological and economic study of IE for 2007–2009 in a French region, using the hospital discharge database (HDD). Methods: The population studied concerned all the patients living in Centre region, France, hospitalized for IE. We extracted hospital stay data for IE from the regional HDD, with a definition based on IE-related diagnosis codes. The predictive positive value (PPV) and sensitivity (Se) of the definition were 87.4% and 90%, respectively, according to the Duke criteria (definite IE frequency 74.4%). Hospitalization costs were estimated, taking into account the fixed hospital charges of the diagnosis-related group (DRG) and supplementary charges due to intensive care unit (ICU) stay. Results: The analysis included 578 patients. The annual average incidence was 45.4 cases per million residents. Valvular surgery was performed in 19.4% of cases. The hospital mortality was 17.6%. Multivariate analysis identified as risk factors for mortality an age ≥ 70 years (odds ratio (OR) = 3.03, 95% confidence interval (CI) = 1.78–5.18), staphylococcal IE (OR = 3.3, 95% CI = 1.9–5.7), chronic renal insufficiency (OR = 2.04, 95% CI = 1.00–4.15), ischemic stroke (OR = 2.55, 95% CI = 1.19–5.47), and hemorrhagic stroke (OR = 5.7, 95% CI = 1.9–17.3). The average cost per episode was $20 103 (€15 281). Conclusions: We report a higher incidence of IE than described by the French national study of 2008. Valvular surgery was considerably less frequent than in the published data, whereas mortality was similar. IE generates substantial costs.